Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

For the polynomial below, -3 and 1 are zeros. Express f (x) as a product of linear factors.

For The Polynomial Below 3 And 1 Are Zeros Express F X As A Product Of Linear Factors class=

Sagot :

Explanation

Since -3 and 1 are zeros of the functions, it implies that

[tex](x+3)\text{ }and\text{ }(x-1)[/tex]

are factors of the equation.

Therefore we can find the remaining factors below

[tex](x+3)(x-1)=x^2+2x-3[/tex]

By long division

[tex]remaining\text{ expression =}\frac{x^4+6x^3+7x^2-8x-6}{x^2+2x-3}=x^2+4x+2[/tex]

By quadratic formula

[tex]\begin{gathered} x_{1,2}=\frac{-4\pm\sqrt{4^2-4\times1\times2}}{2\times1} \\ x_1=\frac{-4+2\sqrt{2}}{2},x_2=\frac{-4-2\sqrt{2}}{2} \\ x=-2+\sqrt{2},x=-2-\sqrt{2} \\ therefore \\ (x+2-\sqrt{2})(x+2+\sqrt{2}) \end{gathered}[/tex]

The linear factor are

Answer:

[tex]f(x)=(x+3)(x-1)(x+2-\sqrt{2})(x+2+\sqrt{2})[/tex]